2021
DOI: 10.1016/j.brs.2020.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Direct electrical stimulation evidence for a dorsal motor area with control of the larynx

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…As noted early on by Wilson et al (2004), although sensory speech activations overlap with motor speech activations in BA 4, peak sensory activation occurs about 5 mm anterior to peak motor activations (i.e,in BA 6). Intracranial studies have consistently implicated this gyral component of dLMC in speech perception and production (Belkhir et al, 2021;Berezutskaya et al, 2020;Bouchard et al, 2013;Breshears et al, 2015;Chang et al, 2017;Chang et al, 2013), particularly with respect to encoding and production of vocal pitch (Cheung et al, 2016;Dichter et al, 2018). This work dovetails with the present study in which we have identified a region of left dPM that: (a) co-locates with gyral dLMC (Figure 6); (b) responds vigorously to vocal pitch (Figure 3); (c) shows maximum functional connectivity with core regions of the auditory cortex that also respond vigorously to vocal pitch; and (d) shows strong acoustically driven tuning within speech trials rated as unintelligible.…”
Section: Left Dpm: Encoding Of Vocal Pitch In the Dorsal Laryngeal Motor Cortexmentioning
confidence: 98%
See 1 more Smart Citation
“…As noted early on by Wilson et al (2004), although sensory speech activations overlap with motor speech activations in BA 4, peak sensory activation occurs about 5 mm anterior to peak motor activations (i.e,in BA 6). Intracranial studies have consistently implicated this gyral component of dLMC in speech perception and production (Belkhir et al, 2021;Berezutskaya et al, 2020;Bouchard et al, 2013;Breshears et al, 2015;Chang et al, 2017;Chang et al, 2013), particularly with respect to encoding and production of vocal pitch (Cheung et al, 2016;Dichter et al, 2018). This work dovetails with the present study in which we have identified a region of left dPM that: (a) co-locates with gyral dLMC (Figure 6); (b) responds vigorously to vocal pitch (Figure 3); (c) shows maximum functional connectivity with core regions of the auditory cortex that also respond vigorously to vocal pitch; and (d) shows strong acoustically driven tuning within speech trials rated as unintelligible.…”
Section: Left Dpm: Encoding Of Vocal Pitch In the Dorsal Laryngeal Motor Cortexmentioning
confidence: 98%
“…While it is not clear whether such tuning would emerge in the right dPM with different stimuli, a different task, or a larger sample, it has been shown convincingly at the meta-analytic scale that activation to heard speech is strongly left biased in the premotor cortex (Buchsbaum et al, 2011). However, intracranial studies have shown that both left and right dLMC respond during speech perception and production (Belkhir et al, 2021;Berezutskaya et al, 2020;Dichter et al, 2018). Thus, the issue of hemispheric laterality in dPM/dLMC during speech perception merits further investigation.…”
Section: Left Dpm: Encoding Of Vocal Pitch In the Dorsal Laryngeal Motor Cortexmentioning
confidence: 99%
“…As noted early on by Wilson et al (2004), although sensory speech activations overlap with motor speech activations in BA 4, peak sensory activation occurs about 5 mm anterior to peak motor activations (i.e, in BA 6). Intracranial studies have consistently implicated this gyral component of dLMC in speech perception and production (Belkhir et al, 2021;Berezutskaya et al, 2020;Bouchard et al, 2013;Breshears et al, 2015;Chang et al, 2017;Chang et al, 2013), particularly with respect to encoding and production of vocal pitch (Cheung et al, 2016;Dichter et al, 2018). This work dovetails with the present study in which we have identified a region of left dPM that: (a) co-locates with gyral dLMC (Figure 7); (b) responds vigorously to vocal pitch (Figure 4); (c) shows maximum functional connectivity with core regions of the auditory cortex that also respond vigorously to vocal pitch; and (d) shows strong acoustically driven responses within speech trials rated as unintelligible.…”
Section: Left Dpm: Sensitivity To Vocal Pitch In the Dorsal Laryngeal Motor Cortexmentioning
confidence: 98%
“…Further, it has been suggested that dLMC preferentially controls the extrinsic muscles of the larynx, which move the entire larynx vertically within the airway and play a key role in complex pitch modulations of the sort common in human speech and singing; conversely, the vLMC preferentially controls the intrinsic muscles of the larynx, which perform rapid tensioning and relaxation of the vocal folds at the onset and offset of vocalizations (i.e., serve as a coarse 'on-off' switch for phonation; Eichert et al, 2020; but see Belyk et al, 2020;Belyk & Brown, 2014). Interestingly, stimulation of vLMC produces speech arrest (Chang et al, 2017) while stimulation of dLMC produces involuntary vocalization and disruption of fluent speech (Belkhir et al, 2021;Dichter et al, 2018), and dLMC appears to be selectively involved in producing fast pitch changes of the sort that generate stress patterns within a sentence (Dichter et al, 2018).…”
Section: Left Dpm: Sensitivity To Vocal Pitch In the Dorsal Laryngeal Motor Cortexmentioning
confidence: 99%
“…But there is also evidence for a possible hemispheric dissociation of song/prosody production versus production of other aspects of speech and language that remain to be sorted (Ozdemir, Norton, & Schlaug, 2006;Royal, Lidji, Theoret, Russo, & Peretz, 2015). Moreover, several recent direct cortical stimulation/recording studies suggest responses to acoustic speech features and laryngeal production in left and right dPMSA/dLMC (Belkhir et al, 2021;Berezutskaya, Baratin, Freudenburg, & Ramsey, 2020;Dichter et al, 2018;Hamilton, Edwards, & Chang, 2018). We leave these and other questions to future study.…”
Section: Summary and Outstanding Questionsmentioning
confidence: 89%